Study of Solid Medical Waste Management in Aimere Public Health Center, Ngada Regency - Maria Hildaburga Wua; Tadeus A. L. Regaletha; Masrida Sinaga (Universitas Nusa Cendana, 2021)
Public Health Center is one of the health service units which produces solid medical waste. The results of preliminary data collection indicate that the management of solid medical waste at Aimere Public Health Center is still problematic. The Public Health Center does not provide a means of transporting waste and does not have an incinerator to manage this waste, so there is still a build for the management of solid medical waste at the final disposal site. The management of the solid medical waste process starts from separation, labeling, transportation, storage to disposal/destruction. This study aimed to determine the management of solid medical waste in Aimere Public Health Center, Ngada Regency. This qualitative research used the descriptive survey method. Data collected from Aimere Public Health Center in January-March 2021. Sampling used a purposive sampling technique. The number of informants in this study was 7 people, whose positions and duties were related to medical waste management at Aimere Public Health Center. The results showed that at the sorting stage, medical and nonmedical waste was separated the collection was carried out in each action room, at the transportation stage there were no special tools available according to standards, at the temporary storage stage did not use standard container covers, and at the final destruction stage did not use incinerators according to standards. Aimere Public Health Center should improve the processing of solid medical waste, by providing special tools for transporting the waste, temporary shelters according to standards, and final waste disposal sites).